Mini-seminar project: An authentic assessment practice in speaking class for advanced students - Afrianto Daud; Raqib Chowdhury; Mahdum Mahdum; M. Nur Mustafa (Intelektual Pustaka Media Utama, 2020)
This paper reports one best-practice in assessing the public speaking performance of advanced students at an Indonesian public university. The study involves an English course for an advanced class which was primarily related to public speaking skills. Considering that speaking is a productive skill that should be assessed through authentic assessment principles, the lecturers decided to assign the students with a mini-seminar project as part of their final examination. This project required the students to conduct a real-life contextualised seminar in which the organisers, speakers, and audience are composed of the students themselves. This paper discusses the rationale behind the planning and implementation of this successful project which involved a synthesis of assessment of, for, and as learning and critically evaluates the procedures of the assessment, the rubric developed therein, and the challenges experienced by the lecturers within the classroom. After the implementation, it can be concluded that this mini-seminar project as a doable alternative authentic assessment model that is applcable in a speaking class which focuses on the development of students’ public speaking skills. This mini-seminar project is recommended not only because it can be used as an alternative assessment model, but also it encourages students to work together in teams, and encourage them to work creatively, create something new in order to perform better.